African horse sickness - (:unkn) unknown (My University, 2015)
African horse sickness (AHS) is a devastating disease of equids caused by an arthropod-borne virus belonging to the Reoviridae family, genus Orbivirus. It is considered a major health threat for horses in endemic areas in sub-Saharan Africa. African horse sickness virus (AHSV) repeatedly caused large epizootics in the Mediterranean region (North Africa and southern Europe in particular) as a result of trade in infected equids. The unexpected emergence of a closely related virus, the bluetongue virus, in northern Europe in 2006 has raised fears about AHSV introduction into Europe, and more specifically into AHSV-free regions that have reported the presence of AHSV vectors, e.g. Culicoides midges. North African and European countries should be prepared to face AHSV incursions in the future, especially since two AHSV serotypes (serotypes 2 and 7) have recently spread northwards to western (e.g. Senegal, Nigeria, Gambia) and eastern Africa (Ethiopia), where historically only serotype 9 had been isolated. The authors review key elements of AHS epidemiology, surveillance and prophylaxis.
Keywords: African Research